Exploring RPA1-ETAA1 axis via high-throughput data analysis: implications for PD-L1 nuclear translocation and tumor-immune dynamics in liver cancer - Qin, Gaofeng; Chen, Zengkuan; Tian, Weihong; Chen, Hongbo; Zhang, Yu; Wei, Wangzhi (Frontiers in Immunology, 2024)
IntroductionETAA1 is recruited to DNA damage sites via its RPA -binding and ATR -activating domain (AAD) motifs, where RPA binding is crucial for ETAA1’s regulation of ATR activity. Methods & resultsOur findings associate Programmed Death- Ligand1 (PD-L1) with the RPA1-ETAA1 axis, suggesting that upregulated RPA1 -dependent ETAA1 may facilitate PD-L1 nuclear accumulation. We observed strong correlations between ETAA1 and RPA1 with the components involved in HDAC2-mediated deacetylation, clathrin -dependent endocytosis, and PD-L1 nucleocytoplasmic shuttling, aligning with the established regulatory pathway of PD-L1 nuclear translocation. Moreover, nuclear PD-L1 transactivates a panel of pro-inflammatory and immune response transcription factors, potentially reshaping the tumor immune microenvironment. We identified a landscape of infiltrating lymphocytes influenced by ETAA1, finding that levels of ETAA1 were negatively correlated with CD8+ T and Natural Killer T (NKT) cells, but positively correlated with CD4+ T helper 2 (Th2) cells, cancer-associated fibroblasts (CAFs), myeloid-derived suppressor cells (MDSCs), neutrophils and regulatory T cells (Tregs), suggesting a potential role in immune evasion. Further analysis shows that the RPA1-ETAA1 axis is significantly associated with multiple metastasis mediators and unfavorable liver cancer progression, with higher expression observed in advanced stages and poorly differentiated subgroups. Discussion & conclusionThese findings expand the role of the RPA1-ETAA1 axis beyond DNA repair, highlighting its potential as a target for cancer therapy.